MIDAS-OWL: An Ontology for Interoperability between Data and Service Cloud Layers - Ribeiro, Elivaldo Lazer Fracalossi; Souza, Marlo; Claro, Daniela Barreira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
As different cloud computing services have emerged over the years, the diversity of technologies and the lack of standardization has given rise to an interoperability problem in cloud computing. Cloud computing services include those such as Software as a Service (SaaS), Platform as a Service (PaaS), Infrastructure as a Service (IaaS), and Data as a Service (DaaS). In this context, interoperability enables a service to communicate with another service transparently. Among the solutions proposed in the literature, a middleware can be used to intermediate such communication and to mitigate the lack of interoperability in cloud computing. For instance, the middleware MIDAS (Middleware for DaaS and SaaS) provides transparent interoperability between SaaS and DaaS. Although MIDAS current version promotes syntactic interoperability, semantic interoperability is only superficially addressed. In collaboration with this project, we develop an OWL-based ontology to formally represent the communication between SaaS and DaaS, and discuss its strengths in providing semantic interoperability on MIDAS. We conduct a set of experiments to validate our ontology. We evaluate intrinsic (consistency, correctness, acceptance) and extrinsic (integration between ontology and MIDAS) issues. Results provide evidence that a semantic MIDAS interoperability can be enhanced by our ontology.